Technical feasibility and safety of image‐guided parieto‐occipital ventricular catheter placement with the assistance of a wearable head‐up display. Issue 4 (19th May 2017) - Yoon, Jang W.; Chen, Robert E.; ReFaey, Karim; Diaz, Roberto J.; Reimer, Ronald; Komotar, Ricardo J.; Quinones‐Hinojosa, Alfredo; Brown, Benjamin L.; Wharen, Robert E.
Abstract: Background: Wearable technology is growing in popularity as a result of its ability to interface with normal human movement and function. Methods: Using proprietary hardware and software, neuronavigation images were captured and transferred wirelessly via a password‐encrypted network to the head‐up display. The operating surgeon wore a loupe‐mounted wearable head‐up display during image‐guided parieto‐occipital ventriculoperitoneal shunt placement in two patients. Results: The shunt placement was completed successfully without complications. The tip of the catheter ended well within the ventricles away from the ventricular wall. The wearable device allowed for continuous monitoring of neuronavigation images in the right upper corner of the surgeon's visual field without the need for the surgeon to turn his head to view the monitors. Conclusions: The adaptable nature of this proposed system permits the display of video data to the operating surgeon without diverting attention away from the operative task. This technology has the potential to enhance image‐guided procedures.